2009
DOI: 10.4141/cjps08217
|View full text |Cite
|
Sign up to set email alerts
|

Influence of six successive annual applications of sulphur fertilizers on wheat in a wheat–canola rotation on a sulphur deficient soil

Abstract: . 2009. Influence of six successive annual applications of sulphur fertilizers on wheat in a wheat Á canola rotation on a sulphur-deficient soil. Can. J. Plant Sci. 89: 629Á644. A 9-yr (1999Á2007) field experiment was conducted on a S-deficient Gray Luvisol (Typic Cryoboralf) loam soil at Porcupine Plain in northeastern Saskatchewan. The objective was to compare the influence of six successive annual applications (1999Á2004) and the following residual effects for 3 yr (2005Á2007) of elemental S and sulphate-S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…1). Malhi et al (2009) showed no benefit of S fertilizer to yield, which, along with our study, implies that the effect of S fertilizer is questionably beneficial. It is possible that the small S fertilizer effect across sites was due to undetected site by S fertilizer interactions; also, that S requirements for CWRS and durum wheat in western Canadian soils are low, or that the applied rate of 25 kg SO 4 -S ha (1 was not sufficient to correct S deficiency, or criteria based on SO 4 -S levels are inadequate.…”
Section: Wheat Yieldsupporting
confidence: 46%
See 1 more Smart Citation
“…1). Malhi et al (2009) showed no benefit of S fertilizer to yield, which, along with our study, implies that the effect of S fertilizer is questionably beneficial. It is possible that the small S fertilizer effect across sites was due to undetected site by S fertilizer interactions; also, that S requirements for CWRS and durum wheat in western Canadian soils are low, or that the applied rate of 25 kg SO 4 -S ha (1 was not sufficient to correct S deficiency, or criteria based on SO 4 -S levels are inadequate.…”
Section: Wheat Yieldsupporting
confidence: 46%
“…Prairie soils normally contain sufficient S to optimize wheat production (Alberta Agriculture, Food and Rural Development 2006). Malhi et al (2009) conducted a long-term field experiment on a S-deficient Gray Luvisolic loam soil in northeastern Saskatchewan. These researchers found no effect of timing of S application on seed yield and protein concentration in any year, except that autumn application was superior to spring application for straw yield and S uptake in the first year of the experiment, and for seed total S concentration and S uptake in the second year.…”
mentioning
confidence: 99%
“…However, the N grain content was not efficiently converted into either protein or yield, since both NUtE and grain protein concentration were lower under S fertilization without any significant effect on yield. On the other hand, also under conventional system, the effect of S on wheat protein concentration and yield is controversial [14,17,[43][44][45][46][47][48]. Although several studies have reported a positive effect of S fertilizations under water stress conditions [49][50][51], we found a decrease in pre-anthesis N uptake, N translocation, N grain content, and grain protein concentration in the drier GS2 under CTR + S. On the contrary, the joint N and S foliar fertilization (CTR + NS) increased pre-anthesis N uptake, N translocation, NUtE and grain yield, demonstrating their positive and additive effect [52], under water stress conditions.…”
Section: Growing Season × Fertilization Strategy Effectsmentioning
confidence: 99%
“…Similar to P, wheat response to applied S in the 5 yr rotation was apparently influenced by reduced biological N fixation associated with S exclusion during the hay phase. In both rotations, wheat response to S was comparable although slightly lower than response to P. Wheat has not generally been observed to respond to applied S in western Canada (Grant et al 2004;Karamanos et al 2013b), but there have been reports of wheat response to applied S in a dark gray Luvisol in Saskatchewan (Malhi et al 2009). These results suggest that long-term intensive rotations, especially containing forages, will eventually draw down soil S to critical levels if not replaced.…”
Section: Rotation Effects On Wheat Response To Applied Nutrientsmentioning
confidence: 86%